Is Market Trends and Sentiment Affected Stock Price? Evidence from Energy Sector in Indonesia - Ayunda Rizqi Oktaviana; Anak Agung Gde Satia Utama (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study investigates the relationship between market trends, market sentiment, and stock prices within the energy sector listed on the Indonesia Stock Exchange (IDX). Grounded in behavioral finance theory which emphasizes the influence of psychological and behavioral factors on financial decision-making this research evaluates how fluctuations in public interest and investor sentiment affect stock price dynamics. The study utilizes secondary data extracted from company annual reports, stock price records, and publicly available financial statements covering the period from 2014 to 2023. The sample includes 22 energy sector companies, selected through purposive sampling based on predefined criteria. To measure market trends, the study employs Google Trends scores, while social media sentiment analysis—using Brandwatch—captures investor sentiment. The regression analysis investigates the influence of both variables on stock prices, incorporating control variables such as company size, debt-to-equity ratio, and dividend payout ratio. The empirical findings reveal that both market trends and investor sentiment exert a significant and positive influence on stock prices in the Indonesian energy sector. The implications of these findings extend to several domains. Investors can integrate trend and sentiment indicators into their analytical frameworks to improve decision-making and anticipate stock movements more effectively. Financial analysts and advisors can adopt these behavioral metrics as complementary tools alongside traditional valuation methods.